A Balanced Team Wins Championships: 66 Years of Data from the National Basketball Association and the National Football League. Issue 3 (December 2015) - Otten, Mark P.; Miller, Travis J.
Explicitly monitoring one's own actions has been noted as detrimental to the performance of fine motor skills under duress. Offensive skills rather than defensive skills are typically studied in this context. Defensive techniques typically require skills such as footwork and continuous movement, as opposed to more precise, hand–eye coordinated action. Explicit monitoring theory may be less relevant for defensive skills than offensive skills when playing under pressure. Archival data (66 years) for teams and for individual players was compiled from the National Basketball Association (NBA) and the National Football League (NFL). For basketball ( n = 778) and football ( n = 515) teams, regular season offensive and defensive statistics similarly predicted success in the postseason, which was assumed to create more pressure. For individual basketball players ( n = 5, 132), nine indices of offensive (FG, free throw and three-point shooting, offensive win shares, points, and assists) and defensive (defensive win shares, steals, and blocks) production were compared; among these, three-point shooting percentage was least correlated from season to postseason, suggesting it is especially variable under pressure. A balanced basketball or football team that focuses on both offense and defense may be most successful.